Simultaneous assessment of phenolic metabolites in human urine for a specific biomonitoring of exposure to organophosphate and carbamate pesticides - Denghel, Heike; Göen, Thomas (Toxicology Letters, 2018)
Organophosphate pesticides (OPP) and carbamates are still counted among the most prominent agents used for crops protection. Up to date the determination of dialkylphosphates and their thio derivatives in urine is established for the OPP biomonitoring. However, this approach does not provide information on the exposure to specific OPP agents. A lot of OPP as well as some carbamates also provide specific urinary biomarkers indeed. Analytical methods for the determination of phenolic metabolites of OPP and carbamates have already been established by different working groups. However, these approaches only acquire one or few analytes. Therefore, we developed an analytical procedure which enables the simultaneous assessment of a wide spectrum of phenolic metabolites of OPP, carbamates and other pesticides in human urine using GC-MS/MS. The method includes enzymatic hydrolysis, solid phase extraction, derivatization, and subsequent GC-MS/MS analysis. The method showed detection limits between 0.1 and 0.4 μg/l. Variation coefficients ranged from 1 to 9 % for precision in series and 1 % to 13 % for inter-day precision. Furthermore, recovery rates between 87 and 117 % were determined. Compared with other published analytical procedures, the present method enables the simultaneous monitoring of a much broader spectrum of pesticides and biocides whose structures contain aryl moieties with competitive or improved analytical reliability. Furthermore, the suitability of the developed procedure was verified through the successful application to urine samples of pesticide exposed humans.
EVALuna2:35247